Autophagy Inhibits Apoptosis Induced by agrocybe aegerita Lectin in Hepatocellular Carcinoma - Liu, Wei; Yu, Guojun; Yu, Wenhui; Ye, Xiangdong; Jin, Yanxia; Shrestha, Alok; Yang, Qing; Sun, Hui (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Lectins are carbohydrate-binding proteins that exhibit remarkable antitumor activities by inducing apoptotic or autophagic cell death. However, the relationship between apoptosis and autophagy induced by lectins has rarely been reported. Agrocybe aegerita lectin (AAL), a lectin isolated from the fungus Agrocybe aegerita, exerts antitumor activity through apoptosis. Objective: To study the relationship between the autophagy and apoptosis induced by AAL in hepatocellular carcinoma (HCC) cells, and then to promote the antitumor effect of AAL. Method: AAL was evaluateted using the CCK-8 kit and the trypan blue assay. Cell autophagy was studied using western blotting, acridine orange straining, transmission electron microscopy, and transient transfection of pEGFPLC3 plasmids. We also evaluated AAL-induced autophagy in Caenorhabditis elegans. Apoptosis was studied using flow cytometry. We also identified the antitumor effects of co-treatment of AAL with chloroquine (CQ) in vitro and in vivo. Results: AAL-treated cell lines showed accumulation of microtubule-associated protein light chain 3 II (LC3-II), formation of EGFP-LC3 puncta and acidic autophagic vacuoles (AVOs), and the induction of autophagosomes. Inhibition of autophagy could enhance apoptosis induced by AAL in HCC cells. Furthermore, co-therapy (AAL and chloroquine) promote antitumor effect of AAL in a murine in situ HCC model. Conclusion: Our findings suggest that inhibition of autophagy exerts a synergistic effect on the antitumor activity of AAL and may be a helpful strategy for reducing the dosage of lectin used in antitumor therapy. The autophagy inhibitor may be a synergist of certain antitumor drugs that can induce both apoptosis and autophagy.
Keywords: hepatocellular carcinoma